ROMAN STYLE QUALITY CHANGES IN EUROPEAN ARCHITECTURE IN X-XII CENTURIES - Akhmedov Tolqin Obidovich; Musajonov Muhammadrasul Alisher ugli (Journals Park Publishing, 2022)
This is article gives a description of the Roman style of monumental building and the buildings built in this style, covering the north of France, Germany and Northern Italy in Western Europe, which had long been in decline in the 11th-12th centuries. The religious socio-political factors that led to the birth of this style are covered. The conflict of the people and the church, which shoots the states on the path of their development, on the path of democracy, and this is covered by their reference to art in binagadianism.